MASKULINITAS DAN KORUPSI PADA MINIATUR: SEBUAH STUDI PENTIGRAF - Melania Shinta Harendika; Cahyaningrum Dewojati (Adabiyyāt: Jurnal Bahasa dan Sastra, 2024)
Pentigraf is a three-paragraph short story produced by a creative writing community called Kampung Pentigraf Indonesia (the Indonesian Pentigraf Village or KPI). By composing Pentigraf, the authors can articulate the social phenomena such as corruption with greater clarity. Since the 1970s, corruption has become a problem in Indonesia. KPI published a Pentigraf anthology entitled Hanya Nol Koma Satu (Only Zero Point One) in 2020 to express concerns about corruption. KPI has more than 3,000 members on Facebook from diverse backgrounds, including female homemakers, who, in this anthology, discuss masculine dominance themes connected to corruption. This study shows how masculine norms and gendered perspectives contribute to the perpetuation of corruption, as articulated through Pentigraf, written by female homemakers. This study gathered the data from fifteen Pentigrafs written by female homemakers. Employing Bourdieu’s theory of masculine domination, this document analysis analyzes the intrinsic structure of pentigraf by homemakers in Hanya Nol Koma Satu to deconstruct how masculine standards correlate with textual representations of corruption. The results show that male characters in the Pentigrafs have the personalities of being desirous and indifferent to the suffering of others because they cling to wealth achievement and supremacy. Pentigraf is a mini-fiction that is not easy to analyze deeply. Nevertheless, it can articulate moral teachings and capture social phenomena.